CONSTITUTIONAL STRUCTURE OF HUMAN RIGHTS IN INDIA - Sonajirao Garje, Balasaheb; Vijaya Singh, Atibha; Yadav, Jitendra (International Journal of Psychosocial Rehabilitation, 2020)
Those rights that are inalienable to us as human beings are known as human rights, and they are described as such. The fact that we are human beings entitles us to make some claims. Human rights in the Indian Constitution are the subject of this study. The purpose of this study is to examine how the Indian judiciary and judicial activism contribute to the preservation of human rights. As a result of its independence, India has played a major role in the defense of human rights worldwide. Although India’s constitution does not have a detailed Bill of Rights, attempts have been undertaken to transform this fact into law. India’s judiciary had a pivotal role in translating these rights into practice.